Piezoelectric Mat as Door Bell - Yuandhana, Genta; Lisdiana, Kania; Ghifari, Rizal Haidar; Shadrina, Syifa Nur; Rusdiana, Dadi; Suwandi, Tri (Indonesian Journal of Multidiciplinary Research, 2021)
Ecological Crisis is a change in world weather which is getting warmer due to the accumulation of CO2 gas in the atmosphere. Burning rock coal which is a source of electricity generation, is a contributor to the effects of the ecological crisis in the world. This caused the world needs new energy sources, such as piezoelectric, etc. The manufacture of piezoelectric mats as house bells aims to show that there is alternative energy for power generation in order to reduce the use of coal in Indonesia. By reducing the use of coal, it will reduce the occurrence of an ecological crisis. The research method we used was an experiment with planning, design and implementation stages. The renewal of this project is to assemble and apply the piezoelectric directly to objects that require electrical energy by replacing the power source from the piezoelectric system, and implementing it for house bells. Piezoelectric mat is a mat that can generate electrical energy if the surface is pressed. This energy can be generated from the piezoelectric that is installed on the inside of the mat. Piezo mats will be installed to be stepped on by guests visiting a house. This foot step will put pressure on the mat. The more tread is obtained, the more electricity is generated. This piezo carpet will be installed in front of the house. The use of piezo mats is an effort to utilize mechanical energy in the form of pressure generated by footrests into electrical energy.